2020
DOI: 10.1515/geo-2020-0119
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tourism activities on water pollution in the West Lake Basin (Hangzhou, China)

Abstract: This paper introduced the development of tourism and its impact on the water environment. Then, taking the West Lake Basin as an example, the change of water quality in the basin between 2007 and 2018 and the changes of tourism population, tourism economic income, and tourism garbage between 2007 and 2018 through Hangzhou Tourism Bureau were investigated to analyze the impact of human tourism activities on the water environment of the West Lake Basin. The results showed that the change in curve trends of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Existing studies have shown that tourism can have adverse effects on the environment. For example, several scholars have revealed that while tourism actively promotes the development of the economy, it also causes adverse effects in terms of water pollution [21,22]. In addition, several studies have found that negative impacts on the environment and biodiversity are most pronounced near tourist resorts [23,24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Existing studies have shown that tourism can have adverse effects on the environment. For example, several scholars have revealed that while tourism actively promotes the development of the economy, it also causes adverse effects in terms of water pollution [21,22]. In addition, several studies have found that negative impacts on the environment and biodiversity are most pronounced near tourist resorts [23,24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…We also found that the growth rate of the TWF was consistently larger than that of tourism revenue and that the two were not synchronous, indicating that tourism water consumption was not effectively controlled in the 2013-2018 period. This unsynchronized trend also appeared in the development of West Lake tourism; tourism revenue increased by 21% while tourism waste increased by 55% [18]. This series of phenomena is contrary to the goal of water conservation in tourism.…”
Section: Spatial and Temporal Differences In The Twfmentioning
confidence: 97%
“…LMDI analysis allowed the identification of the driving forces that affected the changes in the TWF of each province, based on which tourism water use policies can be formulated to reduce regional disparities. Sun and Liu [18] found that the number of tourists and tourism income in West Lake increased water pollution, which means that the grey water footprint increased. Similarly, the growth of the TWF in China was mainly driven positively by the number of tourists and per capita tourist expenditure; however, the driving effect weakened continuously, probably due to the increase in the proportion of elderly tourists and the change in the structure of tourist expenditure.…”
Section: Twf Driving Factorsmentioning
confidence: 99%
“…Normally, the model of panel data contains three types. Failure to select the appropriate model will make the result quite different, so the model checking work must be completed [20,21]. First, we choose the F test method to test, and if the result shows that the null hypothesis is rejected, the model can be selected.…”
Section: Model Constructionmentioning
confidence: 99%